Chronic high-dose beetroot juice supplementation improves time trial performance of well-trained cyclists in normoxia and hypoxia - Rokkedal-Lausch, T.; Franch, J.; Poulsen, M. K.; Thomsen, L. P.; Weitzberg, E.; Kamavuako, E. N.; Karbing, D. S.; Larsen, R. G. (Nitric Oxide, 2019)
Highlights